Membentuk kepercayaan publik melalui strategi public relations dalam industri perbankan - NOPANDIRGA, BAYUDA ZAKY (Maliki Interdisciplinary Journal, 2025)
Public trust is a fundamental aspect of maintaining the reputation and sustainability of banking institutions. In an era of increasing competition and rapid digital development, banks are required not only to provide quality services but also to manage their image and public relations strategically. This study aims to describe how Public Relations (PR) strategies play a role in building public trust in the Indonesian banking industry. The method used is a literature review analyzing several relevant Indonesian journals concerning PR strategies, customer trust, and institutional reputation. The findings show that public trust can be strengthened through transparent communication, the use of digital media, professional crisis management, and effective social responsibility programs. Public Relations acts as a key link between banking institutions and the public in building a positive image and fostering public trust.